Technology road mapping for quantum computing and engineering - Mishra, Brojo Kishore, 1979- (Engineering Science Reference, 2022)
"The aim of the book is to publish in all the aspects of quantum computing concepts, engineering, technologies, operations, and applications from basics to future advances"--